A Randomized Waitlist-controlled Pilot Trial of Voice over Internet Protocol-delivered Behavior Therapy for Youth with Chronic Tic Disorders - Ricketts, Emily J. (J Telemed Telecare, 2015)
INTRODUCTION: Comprehensive Behavioral Intervention for Tics (CBIT) has been shown to be efficacious for Chronic Tic Disorders (CTDs), but utilization is limited by a lack of treatment providers and perceived financial and time burden of commuting to treatment. A promising alternative to in-person delivery is Voice over Internet Protocol (VoIP), allowing for remote, real-time treatment delivery to patients’ homes. However, little is known about the effectiveness of VoIP for CTDs. Therefore, the present study examined the preliminary efficacy, feasibility, and acceptability of VoIP-delivered CBIT (CBIT-VoIP). METHODS: Twenty youth (8–17) with CTDs participated in a randomized, waitlist-controlled pilot trial of CBIT-VoIP. The main outcome was pre- to post-treatment change in clinician-rated tic severity (Yale Global Tic Severity Scale). The secondary outcome was clinical responder rate (Clinical Global Impressions – Improvement Scale), assessed using ratings of ‘very much improved’ or ‘much improved’ indicating positive treatment response. RESULTS: Intention-to-treat analyses with the last observation carried forward were performed. At post-treatment (10-weeks), significantly greater reductions in clinician-rated, [F (1, 18) = 3.05, p < 0.05, partial η(2) = 0.15], and parent-reported tic severity, [F (1, 18) = 6.37, p < 0.05, partial η(2) = .26] were found in CBIT-VoIP relative to waitlist. One-third (N = 4) of those in CBIT-VoIP were considered treatment responders. Treatment satisfaction and therapeutic alliance were high. Discussion: CBIT can be delivered via VoIP with high patient satisfaction, using accessible, low-cost equipment. CBIT-VoIP was generally feasible to implement, with some audio and visual challenges. Modifications to enhance treatment delivery are suggested.